Comparative analysis of the reproductive strategy of lion's paw scallop Nodipecten subnodosus in Baja California Sur, Mexico - Marco A Angel-Dapa; Marcial Arellano-Martinez; Bertha P Ceballos-Vázquez; Hector Acosta-Salmón; Pedro E Saucedo (Latin American Journal of Aquatic Research, 2015)
The reproductive strategy of lion's paw scallop Nodipecten subnodosus was evaluated in a culturing system in Bahía Tortugas, Baja California Sur, Mexico during an annual cycle, comparing its response with data previously reported at other localities. High frequencies of ripe gonads throughout the year indicate that reproduction was continuous, with two main ripening/spawning events: July-September and December-March. A continuous breeding is also reported for the species in Bahía Magdalena, Bahía Juncalito, and Bahía de Los Angeles. These eutrophic areas are Biological Active Centers where gametogenesis appears to be regulated by the energy taken from recently ingested food following an opportunistic strategy. However, the digestive gland index decreased and the muscle indices increased during one of the breeding peaks, suggesting that some stored reserves are also used to sustain gametogenesis (conservative strategy) partially. High incidences of atretic oocytes are likely associated with atypical daily variations in water temperature from May through September (12 to 33°C), or with stressful conditions in the culturing system in summer. Despite this, the culturing system set in Bahía Tortugas appears beneficial for a continuous reproduction of N. subnodosus.